Strategi Pengelolaan Ekowisata Hutan Mangrove Berkelanjutan Berbasis Ecopreneurship di Kota Makassar Sulawesi Selatan - Amal Arfan; Rosmini Maru; Syafruddin Side; Suhartono Nurdin; Muhammad Faisal Juanda (Faculty of Forestry Universitas Gadjah Mada, 2022)
Mangrove forests provide various tropical and subtropical ecosystem services to support sustainable development and people's livelihoods. Ecopreuneurship-based management became an alternative approach for mangrove forests ecotourism. Implementing the ecopreneurship concept in mangrove forest areas could include the utilization of mangrove forest products for business while maintaining biodiversity and the environmental sustainability of the ecosystem. This research aimed to formulate the strategy for ecopreneurship-based management of mangrove forests. This research employed direct observation and in-depth interviews. The respondents were purposively selected based on their specific roles within the communities, community leaders, local governments, and non-governmental organizations surrounding the mangrove forest areas. This research applied SWOT (Strengths, Weaknesses, Opportunities, and Threats) method to analyze the ecopreneurship-based mangrove ecotourism management in Makassar City. The SWOT analysis resulted in three strategies to capture the available opportunities. First, developing community business through innovations in local resource utilization. Second, empowering the community groups such as fishermen, farmers, and women to create mangrove-based household scale businesses. Third, providing training on the post-harvesting mangrove forest products and digital/ online marketing for brown sugar.